(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article, based on the study of the characteristics of the development of the trend of integration of modern scientific knowledge, the identification of its main laws, the increase in the speed and complexity of the integration processes corresponding to the exponential growth of the main components of the specialization modules, the unevenness of the integration process, the change of specific integrating factors, scientific- current issues such as increasing the progressive role of integration in the development of technical and social development are highlighted.